Remodeling of extracellular matrix due to solid stress accumulation during tumor growth. (3rd September 2015) - Pirentis, Athanassios P.; Polydorou, Christiana; Papageorgis, Panagiotis; Voutouri, Chrysovalantis; Mpekris, Fotios; Stylianopoulos, Triantafyllos
Abstract: Solid stresses emerge as the expanding tumor displaces and deforms the surrounding normal tissue, and also as a result of intratumoral component interplay. Among other things, solid stresses are known to induce extensive extracellular matrix synthesis and reorganization. In this study, we developed a mathematical model of tumor growth that distinguishes the contribution to stress generation by collagenous and non-collagenous tumor structural components, and also investigates collagen fiber remodeling exclusively due to solid stress. To this end, we initially conducted in vivo experiments using an orthotopic mouse model for breast cancer to monitor primary tumor growth and derive the mechanical properties of the tumor. Subsequently, we fitted the mathematical model to experimental data to determine values of the model parameters. According to the model, intratumoral solid stress is compressive, whereas extratumoral stress in the tumor vicinity is compressive in the radial direction and tensile in the periphery. Furthermore, collagen fibers engaged in stress generation only in the peritumoral region, and not in the interior where they were slackened due to the compressive stress state. Peritumoral fibers were driven away from the radial direction, tended to realign tangent to the tumor–host interface, and were also significantly stretched by tensile circumferential stresses. By means of this remodeling, the model predicts that the tumor is enveloped by a progressively thickening capsule of collagen fibers. This prediction is consistent with long-standing observations of tumor encapsulation and histologic sections that we performed, and it further corroborates the expansive growth hypothesis for the capsule formation.